The Effect of Shopee Paylater Access Convenience on Purchasing Decisions Moderated by Self-Control Among Gen Z in Surabaya - Nina Rahmadhani; Veni Rafida (Economic Education Analysis Journal, 2026)
This study aims to examine the effect of Shopee Paylater access convenience on purchasing decisions and to analyze the moderating role of self-control among Gen Z consumers in Surabaya. The ease of access offered by digital financial services such as Shpee Paylater has the potential to encourage impulsive purchasing decisions is necessary to help consumers make wiser and more responsible consumption choices. This research uses a quantitative approach with an associative research design to analyze the relationship between variables. The population consisted of Gen Z consumers domiciled in Surabaya totling 707,871 and 130 respondents were selected through purposive sampling. Data were collected using an online questionnaire based on a five point likert scale and anlyzed through Partial Least Square Structural Equation Modelling (PLS-SEM) with SmartPLS 4 software. The result indicate that Shopee Paylater access convenience has a significant positive effect on purchasing decisions, self-control has a significant positive effect on purchasing decisions as the dominant factor, and self-control significantly moderates and strengthens the effect of access convenience on purchasing decisions among Gen Z consumers in Surabaya. These findings suggest that both technological convenience and psychological readiness play an important role in shaping purchasing behavior among Gen Z consumers. This study contributes to the development of digital consumer behavior research and provides insights for businesses and educational institutions in encouraging wiser and more responsible purchasing decisions.